Investigations on fire‐gilding. (4th July 2022) - Margreiter, Raphael; Baumann, Jonas; Mantouvalou, Ioanna; Radtke, Martin; Reinholz, Uwe; Strub, Erik
Abstract: Fire‐gilding is a historic technique for the application of golden layers on a number of different base materials utilizing a gold amalgam. This technique leaves a significant amount of Hg in the golden layer, giving archeometrists a reliable indicator to identify fire‐gildings. Recent findings on presumably fire‐gilded objects have shown in several cases significantly lower Hg content than previously studied objects. This prompted a synchrotron‐based X‐ray fluorescence investigation into the Hg distribution along the material–gilding interface, as well as a series of measurements regarding the Hg content development in fire‐gilded samples during artificial aging. This work presents findings on laboratory‐prepared fire‐gildings, indicating an Hg enrichment at the interface of fire‐gilded silver samples. Notably, such an enrichment is missing in fire‐gilded copper samples. Further, it is confirmed that fire‐gilded layers typically do not undercut an Hg bulk content of 5%. In this light, it seems improbable that ancient samples that contain <5% Hg are fire‐gilded. The results presented in this study might lead to a non‐destructive method to identify the Hg enrichment at the interface. This might be obtained by a combination of different non‐destructive measurements and might also work unambiguously in samples in which the gold top layer is altered.